Pelatihan Pembuatan Minyak Telon Antinyamuk Sebagai Upaya Perawatan Kesehatan Anak dan Perintisan Home Industri di Surakarta - Ghani Nurfiana Fadma Sari; Endang Sri Rejeki; Mamik Ponco Rahayu; Nuraini Harmastuti; Taufik Turahman; Supriyadi Supriyadi (Journal of Dedicators Community, 2021)
Telon oil and children have been an inseparable unity. The making of telon oil from easy-to-find traditional ingredients can encourage home industry ideas for economic growth. The use of essential oils (orange oil/ lavender oil) as components of the making of telon oil is expected to avoid mosquito bites causing itching and even dengue fever. The community service activity program aims to provide training of anti-mosquito telon oil making to keep children healthy. The participants of the program include a cadre of PKK (Family Welfare Movement) members in RW (Community Unit) 21, Nusukan Village, Banjarsari Sub-district, Surakarta. The community service activity began with the explanation of natural ingredients used to make telon oil as well as their benefits. Afterward, the training was conducted through several stages including a tutorial, technical assistance by the community service team, and evaluation of the activity. The results of the activity are: 1) the participants have an understanding of the benefits of the ingredients used; 2) the participants understand the procedure to make the anti-mosquito telon oil; 3) the participants can make the anti-mosquito telon oil by themselves.